The Effect of Online Games on Learning Motivation and Learning Achievement - Santinah Santinah; Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2022)
Technological developments make online games increasingly known throughout the community as a means for entertainment and even serve as a sport. This study aims to determine the effect of online games on learning motivation and student achievement. The results of the study show that at a certain level online games can be used as motivation to learn, but at the level of addiction to online games, it is very disturbing for students in learning achievement.